City Limits: Female Philanthropists and West Nurses in Seventeenth-Century Scottish Towns - Desbrisay, Gordon (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1997)
AbstractThis paper explores the ways in which women contributed to the complex web of negotiations and accommodations out of which the early modern urban community was formed. Drawing on the archives of seventeenth-century Aberdeen and other Scottish cities, it focuses on female philanthropists and unwed wet nurses, women at the top and bottom, the centre and margins of urban society. Rich women founded hospitals for old women and schools for young girls, but these feminist initiatives did not extend to the female guestworkers in their midst: migrant female domestics made pregnant in town had to fend for themselves, and many ended up wet-nursing the children of the rich. Yet in indirect ways they, too, left their mark on urban society. These stories, then, shed fresh light on the complex and sometimes contradictory ways in which early modern women pursued their collective and individual interests under conditions of profound gender inequality.